HEALTH AND WELLNESS - Kurtadikar, Janaki V.; Gaikwad, Manisha N. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today's time, the concept of health and wellness is considered very important. Both these aspects should be good. Basically, health is the fundamental right of every citizen. This has been stated by the World Organization. So how should this health be, it should also be healthy. So what is healthy? What exactly does it mean to keep our health healthy and peaceful? Also, what should we do to stay healthy? What are the factors that affect health. It is necessary to see which factors are necessary for healthy health. Health, Wellness, Peace, Citizen